(untitled) (Bangladesh Journal of Medical Science, 2025)
Background Arterial hypertension (AH) and post-COVID synrome poses a rising challenge in low and middle-income countries, with uncertain prevalence in Kazakhstan’s older adults population. Objectives This study investigates the effectiveness and safety of transitioning older adults patients (65 and older) from multiple antihypertensive medications to a “single tablet” strategy, aiming to evaluate its effect on patient conidion and identify factors influencing dose adjustments. Design A prospective cohort study with a follow-up of 8 week. Participants There were enrolled 98 patients, categorizing them by age groups 65-74 years and 75 and older. Intervention One-moment isolated deprescribing of hypotensive drugs to “one tablet” therapy. Measurements Endpoints were assessed over three visits in eight weeks, utilizing statistical analysis with significance set at p < 0.05. Results Older patients exhibited a trend of higher education, lower smoking rates, and lower average weight. Transitioning to a single-tablet strategy led to a significant reduction in hypertensive crises and adverse events. While therapy adherence improved initially, it decreased by 10% by the 8th week. Factors influencing therapy changes were identified through subgroup analysis. Conclusion This study provides valuable insights into transitioning older adults patients to a “single tablet” strategy, underscoring the importance of personalized approaches based on identified influencing factors. Bangladesh Journal of Medical Science Vol. 24 No. 01 January’25 Page : 155-163